Legitimacy of Criminal Law in Lieu of Fines in Corruption - Rizki Herman (Universitas Negeri Gorontalo, 2022)
This study aims to analyze the criminal regulation of confinement in lieu of fines in criminal law in Indonesia, as well as to examine whether the application of imprisonment is a substitute for fines in corruption by law enforcement in Indonesia. This type of research in writing this proposal is a normative juridical research method. The approach used in this study is statutory. The results show that law enforcement refers to the provisions of criminal confinement, which are contained in Article 10 of the Criminal Code, which then substitutes for imprisonment in Article 30 and Article 31 of the Criminal Code.